Procedural Ethics for Participatory Research: Field-Specific Dilemmas and Recommendations From Researchers, Co-researching Community Partners and the REC Overseeing a Community-Academic ADHD Research Project - Sarah Cilia Vincenti; Paulann Grech; Michael Galea; Vince Briffa; Sarah Borg Spiteri; Maria Cachia; Sharon Del Bene; Jennifer Briffa Desjardins; Naomi Galea McKay; Mel McElhatton; Herma Privitera Brightwell; Marie Claire Saliba; et al. (International Journal of Qualitative Methods)
Philosophical assumptions of the participatory worldview collide with the biomedical framework on which procedural ethics have been grounded. Consequently, obtaining or approving ethical clearance for participatory research can be challenging. Researchers may resent being pressed to water down participatory features to suit institutional requirements. Co-researching community partners’ trust towards academia may be compromised at the outset if the REC comes across unappreciative of their tacit knowledge or is insensitive to their self-determination appeals. REC members may be conflicted over unfamiliar dilemmas. A report detailing effective collaboration during design and approval of a protocol for a photovoice study aimed to empower ADHD women is provided. This collaboration culminated in study plans which satisfied one and all’s requirements. In an attempt to include co-researcher voice in publications and promote more positive perceptions of REC oversight in participatory scholarship, recommendations by academic and community partners and the REC chair who is overseeing this project are advanced. Many lessons were drawn from this positive experience by those who engaged in it. Ethicality, in the context of participatory research is certainly not straightforward, but its pursuit need not be a battlefield. It requires the mobilization of values embedded in the participatory worldview and, akin to the research itself, holds transformative potential.